Magnetic properties of Sm-Fe-N bulk magnets produced from Cu-plated Sm-Fe-N powder - Tetsuji Saito; Tomoe Deguchi; Hitoshi Yamamoto (AIP Advances, 2017)
In this study, Cu-plated Sm-Fe-N powder was prepared for consolidation by the SPS method. The structures and magnetic properties of Sm-Fe-N bulk magnets produced from the Cu-plated Sm-Fe-N powder were examined. It was found that the powder could be consolidated into bulk materials at low temperatures of 473–673 K. The Sm-Fe-N magnet produced at a temperature of 473K from the Cu-plated Sm-Fe-N powder showed a high coercivity of 9.5 kOe, close to that of the Sm-Fe-N powder.